2018
DOI: 10.3103/s1063455x18030074
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Method of Garment Filtering Purification of Water Objects of Chrome (VI)

Abstract: Разработана мобильная конструкция биоплато для очистки сточных вод от ионов хрома, биотической составляющей которой являются наземные растения. Проведен поиск видов высших наземных растений, в условиях водной культуры обладающими высокой способностью аккумулировать хром, и субстрата, пригодного для роста высших наземных растений в условиях аквакультуры. Изучена поглотительная способность сконструированных биоплато по отношению к хрому (VI). Ключевые слова: биоплато, наземные растения, хром (VI), фитодезакцивац… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The offered approach has allowed us to establish state of the aquatic system under study, make quantitative estimation of technogenic factors and forecast consequences of their influence. This will enable future development of a system of environment protection measures in order to return the technogenically altered aquatic ecosystems to a state of dynamic equilibrium [13,19].…”
Section: Discussion Of the Results Obtained In Calculation Of Ecologimentioning
confidence: 99%
See 1 more Smart Citation
“…The offered approach has allowed us to establish state of the aquatic system under study, make quantitative estimation of technogenic factors and forecast consequences of their influence. This will enable future development of a system of environment protection measures in order to return the technogenically altered aquatic ecosystems to a state of dynamic equilibrium [13,19].…”
Section: Discussion Of the Results Obtained In Calculation Of Ecologimentioning
confidence: 99%
“…Indicators characterizing ecological hydrology of a water body, structural and functional properties of aquatic ecosystems, anthropogenic load on aquatic ecosystems and self-purifying capacity of water were used. Such study approach makes it possible to assess state of a particular area of a water body that needs to be studied and identify sources of anthropogenic influence for taking necessary measures [19]. It is effective when applied to technogenically altered aquatic ecosystems of small and medium rivers, plain areas with temperate continental climate.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated [8] that not only higher aquatic plants are characterized by high accumulation rates, but also terrestrial plants in water culture have the same ability to accumulate toxic substances. The main advantages of this method are low energy consumption, high degree of purification, environmental friendliness and the ability to accumulate various types of pollutants.…”
Section: Introductionmentioning
confidence: 99%